2014
DOI: 10.1074/jbc.m113.501635
|View full text |Cite
|
Sign up to set email alerts
|

scyllo-Inositol Promotes Robust Mutant Huntingtin Protein Degradation

Abstract: Background: Effects of scyllo-inositol, a modulator of misfolded protein accumulation, were tested in a cellular model of Huntington disease. Results: scyllo-Inositol lowered mutant huntingtin aggregation and decreased protein abundance through proteasomal and lysosomal degradation. Conclusion: scyllo-Inositol promotes mutant huntingtin degradation in a model of Huntington disease. Significance: In contrast to other compounds targeting mutant huntingtin aggregation and accumulation, scyllo-inositol promotes ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
0
7
0
1
Order By: Relevance
“…The scyllo-inositol reduction we found in AAS users is intriguing given its large effect size, the trend negative association between lifetime AAS dose and scyllo-inositol levels, and reports that scyllo-inositol can reduce the effects of neurotoxic proteins including β-amyloid, α-synuclein, and huntingtin (Lai et al, 2014; McLaurin et al, 2000; Vekrellis et al, 2009). Given observations that the commonly used AAS 17β-trenbolone and methandienone increase β-amyloid levels in male rats (Ma and Liu, 2015) and enhance β-amyloid toxicity in neuronal cultures (Caraci et al, 2011), it follows that human AAS users may be at increased risk for β-amyloid toxicity, and that this risk could be compounded by scyllo-inositol depletion.…”
Section: Discussionmentioning
confidence: 74%
“…The scyllo-inositol reduction we found in AAS users is intriguing given its large effect size, the trend negative association between lifetime AAS dose and scyllo-inositol levels, and reports that scyllo-inositol can reduce the effects of neurotoxic proteins including β-amyloid, α-synuclein, and huntingtin (Lai et al, 2014; McLaurin et al, 2000; Vekrellis et al, 2009). Given observations that the commonly used AAS 17β-trenbolone and methandienone increase β-amyloid levels in male rats (Ma and Liu, 2015) and enhance β-amyloid toxicity in neuronal cultures (Caraci et al, 2011), it follows that human AAS users may be at increased risk for β-amyloid toxicity, and that this risk could be compounded by scyllo-inositol depletion.…”
Section: Discussionmentioning
confidence: 74%
“…[69] Likewise, scyllo-inositol reduces the number of neuronal aggregates and inclusions containing polyglutamineexpanded huntingtin protein in Huntington disease,a nd does this by reducing the amount of mutant protein produced. [70] Amyloid deposits can also form in the islets of Langerhans and may contribute to the development of diabetes: scyllo-, myo-, and epi-inositols are ineffective in preventing the formation of these amyloid deposits. [71] In rats,s eizures induced by pentylenetetrazole were reduced in severity following the administration of scylloinositol.…”
Section: Scyllo-inositol and Neurological Disordersmentioning
confidence: 99%
“…Although further studies are necessary to clarify whether the low sI signal we found in AAS users reflects low sI concentration, a low sI/Aβ ratio, or a combination of these effects, any of these scenarios -via reduction of sI availability to complex with and help eliminate Aβcould lead to or reflect increased Aβ burdens and risk for developing AD/ADRD. Because sI also prevents clumping of other neurotoxic proteins, including α-synuclein and Huntingtin proteins associated with the development of Parkinson's and Huntington's diseases, respectively (Vekrellis et al, 2009;Lai et al, 2014), the low sI signal we found in long-term supraphysiologic-dose AAS users could indicate that they are at increased risk for developing other neurodegenerative disorders.…”
Section: Supraphysiologic-dose Aas Exposures Are Associated With Neurmentioning
confidence: 83%